Students’ Writing Skill in Diary of the Eighth Semester Students of English Study Program at University of Pasir Pengaraian - Wirda Jannatul Jannah; Rivi Antoni (Journal on Education, 2023)
This research is designed as a descriptive qualitative researchh. The purpose of descriptive qualitative research is to find the result of analysis from what the researcher wants to observe. The purpose of this research was to fine out the students’ writing skill in diary of the eighth semester students of English study program at university of pasir pengaraian. In this research, the researcher took 43% from total population where it means there were 26 students. The Instrumentation used in this research is writing test, the researcher asked the samples to write about their experience in diary format and gave them 45 minutes to write their experience. Based on the students’ writing in diary, the researcher asked the raters to checked their score based on the writing scoring rubric. The result found that students’ writing skill through diary in general can be classified into a good level. It can be seen from their average score in writing diary which had been scored by the raters and then analyzed by the researcher was 71.